The Effect of Corona's Impact on the Community's Economy In The Automotive Marketing Sector Using FIS - Dedi Mahrizon (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Corana is very influential on the economy in Indonesia, especially in the marketing of Automotive Goods. At present, there is a very significant decline in turnover. This resulted in sluggish market prices and a lack of consumer interest in shopping due to declining economic conditions. The problem that occurs is the lack of marketing of goods, especially in the automotive sector. The purpose of this research is to study how to improve the marketing of goods in the automotive sector so that the economy can increase as much as possible. The research method used is descriptive qualitative method. In addition, the Mamdani method uses the AND operator to obtain an inference engine. The Mamdani method has four stages, namely Demand, Supply and Purchase and the output obtained is Income Value. using secondary data sources from research results, references and online news related to research. The results of this study obtained 3 inputs, namely, requests, offers and purchases, the final result obtained was a decision-making system in the form of smooth or not automatic marketing based on the data to be processed. inputs.